SyCip, Grand Old Man of PH business; 96 - Lucas, Daxim L. (Philippine Daily Inquirer, 2017)
SyCip, 96, diedon Saturday night aboard Philippine Airlines Flight No. 123 (MNL/YVR/JFK) as the plane was heading to Vancouver Airport.